2006
DOI: 10.2337/dc06-0268
|View full text |Cite
|
Sign up to set email alerts
|

Is Self-Monitoring of Blood Glucose Appropriate for All Type 2 Diabetic Patients?

Abstract: OBJECTIVE -We sought to determine whether self-monitoring of blood glucose (SMBG) is associated with better glycemic control in type 2 diabetes.RESEARCH DESIGN AND METHODS -We used cross-sectional and longitudinal data from type 2 diabetic participants in the observational, community-based Fremantle Diabetes Study (FDS) who reported SMBG status at study entry (n ϭ 1,286) and annual reviews over 5 years (n ϭ 531).RESULTS -At study entry, 70% of patients performed SMBG, with a median of four tests per week (inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 43 publications
7
49
1
Order By: Relevance
“…16,17 We find that performing SMBG showed a significant impact on the clinical outcomes in both age groups, although patients performing SMBG and patients not performing SMBG had comparable cardiovascular antecedents.…”
Section: -17mentioning
confidence: 84%
“…16,17 We find that performing SMBG showed a significant impact on the clinical outcomes in both age groups, although patients performing SMBG and patients not performing SMBG had comparable cardiovascular antecedents.…”
Section: -17mentioning
confidence: 84%
“…Schwedes et al suggested that meal-related structured SMBG could improve glycemic control in T2DM treated with non-insulin regimen (27). Franciosi et al reported that SMBG could be an important role in metabolic control if it is an integral part of a wider educational strategy devoted the promotion of patient autonomy (28).…”
Section: Discussionmentioning
confidence: 99%
“…1 Although some studies report neither selfmonitoring of blood glucose (SMBG) testing nor its frequency is associated with glycaemic benefit in type 2 diabetic patients, SMBG may still be of value in the identification and prevention of hypoglycaemia and in assisting with dose adjustments in insulin-treated patients. 2 What is clear is that encouraging SMBG in people with diabetes mellitus results in lower complication rates. 3 As the incidence of diabetes continues to increase, the number of people relying on glucose meters for improved glycaemic control will similarly increase.…”
Section: Introductionmentioning
confidence: 99%